Ocular hamartoma in a five‐day‐old calf. Issue 1 (5th January 2021) - Hwang, Hyejin; Kim, Daesik; Hillers, Kim; Kim, Min Su
Abstract: Hamartomas are developed focal malformations that resemble neoplasms, resulting from faulty development in an organ. They are composed of a disorganised mixture of cells and tissues normally found in the area of the body where the growth occurs, and develop and grow at the same rate as adjacent tissues. A five‐day‐old male native Korean calf presented with a left ocular mass, with tissue protruding from the eye. No pain response was elicited on palpation. Based on clinical examination, enucleation was performed. The majority of the mass consisted of bland fibro‐adipose tissue with mild inflammation, and no other abnormalities were noted. Histopathology of the left eye mass was consistent with an ocular hamartoma. The calf recovered well and was discharged from the hospital. The case report is the first known example of an ocular hamartoma manifesting in a newborn calf.